Intraspecific and intracolonial variation in the profile of venom alkaloids and cuticular hydrocarbons of the fire ant Solenopsis saevissima smith (Hymenoptera: Formicidae) - Fox, Eduardo Gonçalves Paterson; Pianaro, Adriana; Solis, Daniel Russ [UNESP]; Delabie, Jacques Hubert Charles; Vairo, Bruno Cunha; MacHado, Ednildo de Alcântara; Bueno, Odair Correa [UNESP] (Hindawi, 2012)
Fire ants are aggressive Neotropical ants that are extensively similar in general biology and morphology, making species identification difficult. Some fire ant species are top-rated pests spreading throughout the world by trade vessels. Many researchers attempted to sort between invasive and native species by using chemical characters, including patterns of venom alkaloids. The present study is the first to report intraspecific variation in some chemical characters, namely, cuticular hydrocarbons and venom alkaloids, within the Brazilian fire ant species Solenopsis saevissima and also reports on within-nest variations among members of different castes. Two different haplotypes (cryptic species) of S. saevissima were clearly identified, one presenting a predominant combination of the venom alkaloids cis- and trans-2-methyl-6-undecylpiperidine with the cuticular hydrocarbons C23, 3-Me-C23, 10-C 25:1, C25, and 3-Me-C25, and the other a predominant combination of cis- and trans-2-methyl-6-tridecenylpiperidine with predominance of 12-C25:1, C25, 11-Me-C25, 3-Me-C25, 13-C27:1, C27, and 13-Me-C 27. Intranest variations revealed that the proportions among these compounds varied sensibly among workers of different sizes, gynes, and males (no alkaloids were detected in the latter). Larva contained vestiges of the same compounds. The recorded chemical profiles are quite different from previous reports with S. saevissima samples from So Paulo. The finds thus support other recent claims that S. saevissima includes cryptic species; the study, moreover, adds the find that they can occur in the same geographical location. © 2012 Eduardo Gonalves Paterson Fox et al.
Keywords: Formicidae; Hymenoptera; Solenopsis; Solenopsis geminata; Solenopsis saevissima